DETERMINANTS OF TAX AVOIDANCE IN INDONESIAN TECHNOLOGY LISTED COMPANIES - Dwianika, Agustine (Jurnal Magister Akuntansi Trisakti, 2024)
This study examines the effect of Profitability (Return On Sales and net Profit Margin), Sales Growth and Business Strategy on Tax Avoidance practices and Financial Distress as moderators suspected of influencing corporate tax avoidance practices. The quantitative method used in this study, multiple linear regression, is the right choice for conducting further analysis, with a range of observations of financial reports on technology companies listed on the Indonesia Stock Exchange (IDX) during 2019-2023, with a purposive sampling technique to ensure obtaining information related to the measurement indicators used, in 15 qualified companies, using IBM SPSS Statistics 26.0. The study concluded that Return On Sales, Net Profit Margin, and Business Strategy influenced Tax Avoidance practices. In contrast, the Sales Growth variable did not influence Tax Avoidance, and Financial Distress only moderated the effect of ROS on Tax Avoidance. In practice, not all management strategies to increase sales absorb too high costs, so financial managers do not choose to practice tax avoidance. The implications of this study are expected to provide an overview to users of financial reports, especially external parties, to assess the firm's performance in complying with its tax obligations based on the factors in this study.